RISK ANALYSIS OF INHALED HEXAVALENT CHROMIUM (Cr6+) EXPOSURE ON BLACKSMITH IN MEKARMAJU VILLAGE BANDUNG REGENCY - Aulia Rosalyn, Fiona
Chromium is stable in the form of trivalent chromium [Cr+3 or Cr (III)] and hexavalent chromium [Cr+6 or Cr (VI)]. Cr3+ is an essential metal for the body while Cr6+ is toxic and carcinogenic (IARC, 1982). Cr is widely used in industry as an mixture compound because it is strong and resistant to corrosion. Grinding and welding processes can cause Cr exposure of workers either through inhalation or dermal. Elevation of the concentration of Cr and creatinine in urine indicate exposure to Cr. ACGIH (2007) states BEI value above 10 mg /g creatinine in urine at the end of shift at the end of the day indicate a Cr exposure. The purpose of this study is to determine the levels of Cr and creatinine in the urine due to exposure to inhalated Cr. This epidemic-cross sectional study conducted in the village of Mekarmaju, Pasirjambu, District of Bandung. Of the total 848 blacksmith, 30 people with certain criteria are included as respondents. The control group consisted of 10 people who are not working as a blacksmith. Cr measurements in air will be conducted by NIOSH method 7600 Issue 2 using a personal sampling pump with PVC filters and analyzed by UV-Visible Spectrophotometer with a wavelength of 540 nm. Measurement of chromium in the urine will be conducted by NIOSH method 8310 Issue 2 and then analyzed by Graphit Furnace AAS. From 30 people of exposed group, 21 people exceeded TLV based on SE01/MENAKER/1997, 15 people exceeded BEI for urinary chromium issued by ACGIH, and 22 people have HI>1 which indicates that chromium in their bodies have the potential to endanger their health. Analysis showed significant differences between exposed and control group by p-value of 0.000 for TLV, CDI, and urinary chromium.